Selling the sacred : from Crossfit to Qanon - Einstein, Mara; Taylor, Sarah McFarland, 1968- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"There's religion in my marketing! There's marketing in my religion! Selling the Sacred explores the religio-cultural and media implications of a two-sided phenomenon: marketing religion as a product and marketing products as religion. What do various forms of religion/marketing collaboration look like in the 21st century and what does this tell us about American culture and society? Social and technological changes rapidly and continuously re-frame religious and marketing landscapes. Crossfit is a "cult." Televangelists use psychographics and data marketing. QAnon is a religion and big business. These are some of the examples highlighted in this collection which engages with themes related to capitalist narratives, issues related to gender and race, and the intersection of religion, politics, and marketing, among other key issues. The innovative contributors examine the phenomenon of selling the sacred, providing a better understanding of how marketing tactics, married with religious content, influence our thinking and everyday lives. While also bringing to light how political, economic, and ideological agendas infuse the construction and presentation of the "sacred," via more traditional religious institutions or consumer-product marketing. By examining religion and marketing broadly, this book offers engaging tools to recognize and unpack what gets sold as "sacred," what's at stake, and the consequences. A go-to resource for those working in marketing studies, religious studies, and media studies, Selling the Sacred is also a must read for religious and marketing professionals"--
Branding, promotion, and religious media -- past and present. From logos to logo and back again : images as transactional objects in the history of Christian devotion / David Morgan -- Spiritual healing for sale : medical pluralism and the commodification of Native American healing traditions / Sarah Dees -- Rex Humbard, psychographics, and the hard sell / John Modern.
Keywords: Business -- Religious aspects; Marketing -- Moral and ethical aspects; Mass media -- Moral and ethical aspects; Consumption (Economics) -- Religious aspects; BUSINESS & ECONOMICS / Marketing / General; RELIGION / General